Preliminary agronomic evaluation of rice (Oryza sativa L.) genotypes under saline soil conditions of Yaguachi, Ecuador - Medina Litardo, Reina (2023)
Soil salinity is considered one of the main abiotic stresses that affect rice cultivation throughout the world. The main objective of this study was to carry out the preliminary agronomic evaluation of five commercial rice varieties (INIAP11, INIAP14, SFL-011, INIAP-FL-Arenillas and Fedearroz-60) under saline soil conditions in Yaguachi, Guayas, Ecuador. A completely randomized block design was used to estimate the agronomic response of the materials by quantifying grain yield t.ha-1 (Yield), number of tillers.m-2 (TN), plant height at harvest (PH), number of panicles.m-2 (NPM), panicle length (PL), number of grains/panicle (NGP), number of filled grains/panicle (NFG), number of vain grains (NVG), weight of 1000 grain (P1000) and content of chlorophyll at 30 (C30D) and 60 (C60D) days. The analysis of variance reflected a high phenotypic diversity among the varieties studied, showing adequate adaptation to the level of salinity contained in the soil used for the study. The INIAP-FL-Arenillas, INIAP14, INIAP11 and FEDEARROZ-60 varieties were the genotypes with the best responses under the study conditions, expressed in higher productivity levels. The results also suggest the need to continue evaluating these varieties with and without saline stress conditions, to discriminate the effect of genotype by environment interaction and confirm the level of tolerance to saline stress present in these genotypes, optimizing the selection of the appropriate germplasm in breeding programs, aiming to obtaining genotypes tolerant to saline soils.